Effect of Internal Financial Policy on Shareholders’ Wealth and Firm Value - MOHAMMAD FAROOQ; DR. ALAM REHMAN; ADIL KHAN; MOHAMMAD BILAL (Journal of Business & Tourism, 2021)
This studyexamines the impact of internal financial policy on share holders’ wealth and firm value. The study uses the data of manufacturing sector firms listed on PSE. The study apply random sampling techniques for the collection of data and total 91 firms selected as sample from different sub sectors in manufacturing sector. Stock price each share and firm value per share were taken as dependent variables whereas retained earnings per share and dividend paid per share used as independent variables and net total asset per share and firm value to book value per share taken as control variables. Panel data of all these variables used to examine the relationship of internal financial policy on stock price and firm value. The findings of this study indicate that dividen payout, retained earnings, and net total assets per share have positive and significant impact on stock price where as firm book value per share ratio has insignificant impact on stock price. Dividend payout shown strong relation with stock price as compare to retained earning. Dividend payout, retained earnings, net total assets per share have positive and significance relation with firm value and firm book value per share ratio has positive butinsignificant relationship with firm value. The study has some policy implications for the users and top management of these firms.